Numerical modeling of wall-to-cluster heat transfer in swirling fluidized beds based on MFiX-DEM approach - Anjun Li; Xiaoyu Li; Xiaogang Xu; Yuekan Zhang; Liyun Zhu; Peikun Liu (Case Studies in Thermal Engineering)
The introduction of a tangential velocity component in swirling fluidized beds enhances mixing and heat transfer. Particle clusters are common mesoscale structures in gas-solid flow systems. This study investigated the dynamic and thermal behaviors of cold particle clusters impacting a high-temperature cylindrical wall under centrifugal effects using the MFiX-DEM approach coupled with particle-scale heat transfer models. The effects of centrifugal force parameters—such as tangential velocity, reactor radius, particle number, diameter, and density—were analyzed. Results indicate that all parameters, except particle density, significantly impact wall-particle collision. Higher heat transfer can be achieved with increased tangential velocity, smaller reactor radius, fewer particle amount, smaller particle diameter, and lower particle density. Thermal characteristics are more susceptible to reaching saturation effects than dynamics. For instance, when the tangential velocity exceeds 0.4 m/s, the increase in heat absorption does not exceed 2.85 %. However, both angular velocity and contact force continue to increase significantly. Finally, the correlation between Reynolds number, Archimedes number, the ratio of cluster size to reactor size, and Nusselt number is established.